Effect of calcination condition on phase formation of zirconium titanate powders synthesized by the solid-state reaction - Anurak Prasatkhetragarn (2018)
Zirconium titanate (ZrTiO4; ZT) powders have been prepared by using a solid-state reaction combined with a vibro-milling technique. The effects of calcination temperature, dwell time and heating/cooling rates on phase formation and morphology of the powders were examined. The calcination temperature and dwell time have been found to show a pronounced effect on the phase formation of the calcined zirconium titanate powders. Additionally, the minor phase of unreacted TiO2tends to form together with ZrTiO4, depending on calcination conditions. It is seen that optimization of calcination conditions can lead to 100% yield of an orthorhombic ZrTiO4.